Sigmoid neoplasm. Closed colon occlusion. Total colectomy. lleosigmoidostomy - Mazza, Milton; Trotschansky, Jose; Müller, Gunter (Cirugía del Uruguay, 1974)
A case of sigmoid neoplasm seen in closed occlusion with non reversible (ischemic) injuries of the right colon is reported. Treated with a total (colectomy) and ileosigmoidostomy. that is in opinion of the authors the best solution in this case.